Trends in the theory that inflammation plays a causal role in tendinopathy: a systematic review and quantitative analysis of published reviews - Michael J Mosca; Mustafa S Rashid; Sarah J Snelling; Shona Kirtley; Andrew Jonathan Carr; Stephanie Georgina Dakin (BMJ Open Sport & Exercise Medicine)
Background/aims The contribution of inflammation to tendinopathy has been debated in the scientific literature. Several factors may contribute to this lack of clarity, including inconsistent definitions of inflammation. We hypothesised that the adoption and/or rejection of a causal link between inflammation and tendinopathy varied as a function of the ‘inflammatory component’ (eg, immune cell and molecular mediators included in published reviews).Methods Twenty data items were collected from each review to determine conclusions about the role of inflammation in tendinopathy, specific definitions of the ‘inflammatory component,’ quality of the review and other potential correlates. Associations between correlates and a review’s conclusion about the role of inflammation in tendinopathy were tested using binomial logistic regression. The database searches retrieved 2261 unique publications: 137 fulfilled inclusion criteria after full text screenings.Results There has been little support for an inflammatory component to tendinopathy until recently (2012–2015). Prior to 2012, the majority of published reviews did not discuss monocytes, macrophages or lymphocytes in tendinopathy; rather they focused on the lack of neutrophils, often referred to as ‘the inflammatory infiltrate’, or immune cells were not discussed. Reviews including monocytes and lymphocytes in their discussions were 5.23 times more likely to conclude inflammation was important than reviews that did not, p<0.001.Conclusions Data collected show growing support for an inflammatory component to tendinopathy, particularly among high-quality reviews and those that used more robust definitions of inflammation. This finding may have implications for explaining dissonance in the literature regarding a causal role for inflammation in the pathogenesis of tendinopathy.